Pan-histone deacetylase inhibitor panobinostat sensitizes gastric cancer cells to anthracyclines via induction of CITED2 - Regel, Ivonne; Burgermeister, Elke; Hofheinz, Ralf-Dieter; Ebert, Matthias (Gastroenterology, 2012)
Background & Aims Chemotherapy modestly prolongs survival of patients with advanced gastric cancer, but strategies are needed to increase its efficacy. Histone deacetylase (HDAC) inhibitors modify chromatin and can block cancer cell proliferation and promote apoptosis. Methods Gastric cancer cell lines were incubated with the HDAC inhibitor LBH589 (Panobinostat, Novartis, Germany); levels of proliferation, apoptosis, histone acetylation, and gene expression were determined. We identified factors downstream of HDAC that regulated chemoresistance. The effects of combination chemotherapy of HDAC inhibitors and anthracyclines were studied in CEA424/SV40 T-antigen (CEA/Tag) transgenic mice, which develop gastric tumors. We analyzed gastric tumor samples from patients using immunohistochemistry. Results HDAC2 was expressed in human gastric cancer cell lines and tumor samples, as well as in gastric tumors from CEA/Tag mice, compared with non-neoplastic gastric tissue. LBH589 inhibited proliferation of cancer cells in vitro. LBH589 down-regulated expression of genes that mediate anthracycline resistance by activating expression of Cbp/p300-interacting transactivator, with Glu/Asp-rich carboxy-terminal domain 2 (CITED2), a gene that mediates sensitivity to chemotherapeutics. Pre-incubation of cells with an HDAC inhibitor and overexpression of CITED2-sensitized gastric cell lines to anthracycline-mediated cell death. In CEA/Tag mice, LBH589 induced tumor-cell expression of CITED2 and increased the efficacy of anthracycline to reduce tumor growth. Levels of CITED2 were increased in gastric tumor samples from patients who had complete responses to epirubicin. Conclusions The HDAC inhibitor LBH589 can overcome the resistance of mouse gastric cancer cells to anthracyclines by inducing expression of CITED2. Levels of CITED2 in gastric tumors correlate with patients' response to epirubicin. LBH589 might be used to increase the response of patients to anthracyclines.